Indian Architecture: Social and Political Challenges - Khalfaoui, Mouez (SORUS S.C. Wydawnictwo i Drukarnia Cyfrowa, 2009)
The objective of this paper is to reassess the central factors which have shaped the Indian architecture. The author puts forward the concept of plurality introduced by Western art historians and argues that the diversity of the Indian architecture should not be explained in terms of religious differences, but in terms of the socio-economical situation in South Asia. He also elaborates on the Hindu caste system and its impact on the Indian architecture.

(Architektura indyjska – problematyka społeczna i polityczna). Niniejszy artykuł stanowi krytyczne spojrzenie na dotychczasowe postrzeganie czynników kształtujących architekturę indyjską. Jej różnorodność przedstawiona jest zgodnie z zachodnią tradycją historii sztuki. Autor udowadnia jednak, że największy wpływ na kształt architektury indyjskiej miała nie religia, a sytuacja społeczno-ekonomiczna południowej Azji. Przedstawia on również hinduski system kastowy i jego wpływ na tamtejszą architekturę.
Keywords: Indian architecture; architektura indyjska